Genomic Profiling Comparison of Germline BRCA and Non-BRCA Carriers Reveals CCNE1 Amplification as a Risk Factor for Non-BRCA Carriers in Patients With Triple-Negative Breast Cancer - Huang, Xin; Shao, Di; Wu, Huanwen; Zhu, Changbin; Guo, Dan; Zhou, Yidong; Chen, Chang; Lin, Yan; Lu, Tao; Zhao, Bin; Wang, Changjun; Sun, Qiang (Frontiers in Oncology, 2020)
Background: Differences in genomic profiling and immunity-associated parameters between germline BRCA and non-BRCA carriers in TNBC with high tumor burden remain unexplored. This study aimed to compare the differences and explore potential prognostic predictors and therapeutic targets. Methods: The study cohort included 21 consecutive TNBC cases with germline BRCA1/2 mutations and 54 non-BRCA carriers with a tumor size ≥ 2 cm and/or ≥1 affected lymph nodes. Differences in clinicopathological characteristics and genomic profiles were analyzed through next-generation sequencing. Univariate Kaplan–Meier analysis and Cox regression model were applied to survival analysis. Immunohistochemistry was used to confirm the consistency between CCNE1 amplification and cyclin E1 protein overexpression. Results: The cohort included 16 and 5 patients with germline BRCA1 and BRCA2 mutations, respectively. Patients with germline BRCA1/2 mutations were diagnosed at a significantly younger age and were more likely to have a family history of breast and/or ovarian cancer. Six non-BRCA carriers (11.11%) carried germline mutations in other cancer susceptibility genes, including five mutations in five homologous recombination repair (HRR) pathway genes (9.26%) and one mutation in MSH3 (1.85%). Somatic mutations in HRR pathway genes were found in 22.22% and 14.29% of the non-BRCA and BRCA carriers, respectively. PIK3CA missense mutation (p=0.046) and CCNE1 amplification (p=0.2) were found only in the non-BRCA carriers. The median tumor mutation burden (TMB) was 4.1 Muts/Mb, whereas none of the cases had high microsatellite instability (MSI). BRCA status did not affect disease-free survival (DFS, p=0.15) or overall survival (OS, p=0.52). CCNE1 amplification was an independent risk factor for DFS in non-BRCA carriers with TNBC (HR 13.07, 95%CI 2.47–69.24, p=0.003). Consistency between CCNE1 amplification and cyclin E1 protein overexpression was confirmed with an AUC of 0.967 for cyclin E1 signal intensity. Conclusions: We found differences in genetic alterations between germline BRCA and non-BRCA carriers with TNBC and a high tumor burden. TMB and MSI may not be suitable predictors of TNBC for immune checkpoint inhibitors. Notably, CCNE1 amplification is a novel potential prognostic marker and therapeutic target for non-BRCA carriers with TNBC. Cyclin E1 may be used instead of CCNE1 to improve clinical applicability.